Relationship between perimenopause symptoms and bone mineral density - Siswishanto Rukmono, Aida Djaswadi Dasuki (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
The menopausal transition or perimenopause is associated with numerous symptoms. Womenentering perimonopause normally have menstrual irregular periods due to an imbalance of serumestradiol. Since the status of estrogen is known as an important determinant of bone massdensity, menopausal symptoms can be an effective indicator of bone status in women. Thisstudy aimed to evaluate the relationship between perimenopause symptoms and bone mineraldensity (BMD). This was an observational study using cross-sectional design conducted duringthree months periode from June to August 2010 in Kalangan Village, Banguntapan, BantulDistrict. Subjects were women between the aged 46-55 years who fulfilled the inclusion andexclusion criteria. After underwent history taking, subjects underwent physical examinationaccording to International Physical Activity Questionnaires (IPAQ). The BMD of subjects wasthan measured using dual-energy X-ray absorptiometry (DEXA). The relationship betweenperimenopause symptoms and BMD was then evaluated using multivariate analysis. The resultsshowed that perimenopause symptoms increase abnormal BMD of subjects 1.38 times higherthan those without perimenopause symptoms (RR=1.38; 95%CI 1.39-13.78; p=0.01). Inconclusion, the perimenopause symptoms is associated with the high proportion of abnormalBMD in women.